1997
DOI: 10.1038/42735
|View full text |Cite
|
Sign up to set email alerts
|

Gln 63 of Rho is deamidated by Escherichia coli cytotoxic necrotizing factor-1

Abstract: The actin cytoskeleton is regulated by GTP-hydrolysing proteins, the Rho GTPases, which act as molecular switches in diverse signal-transduction processes. Various bacterial toxins can inactivate Rho GTPases by ADP-ribosylation or glucosylation. Previous research has identified Rho proteins as putative targets for Escherichia coli cytotoxic necrotizing factors 1 and 2 (CNF1 and 2). These toxins induce actin assembly and multinucleation in culture cells. Here we show that treatment of RhoA with CNF1 inhibits th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
466
1
3

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 508 publications
(487 citation statements)
references
References 22 publications
17
466
1
3
Order By: Relevance
“…CheD is structurally related to the cytotoxic necrotizing factor family of bacterial deamidases (44,45). Deamidation is a posttranslational modification used by multiple bacterial virulence factors to modify the function of eukaryotic host target proteins (39).…”
Section: Evidence For Three Gene-duplication Events In Hopaf1 Evolutimentioning
confidence: 99%
“…CheD is structurally related to the cytotoxic necrotizing factor family of bacterial deamidases (44,45). Deamidation is a posttranslational modification used by multiple bacterial virulence factors to modify the function of eukaryotic host target proteins (39).…”
Section: Evidence For Three Gene-duplication Events In Hopaf1 Evolutimentioning
confidence: 99%
“…Binding of ADP-ribosylated RhoA to GDI is increased, which leads to a cytosolic accumulation of inactive RhoRhoGDI complex ("trapping effect") Studies from recent years identified Rho GTPases as the preferred targets of several bacterial toxins. In addition to the ADP-ribosylation by C3, Rho GTPases are covalently modified by glucosylation (e.g., by clostridial glucosylating toxins; Aktories and Barbieri 2005;Just et al 1995b;Aktories and Just 2005;Voth and Ballard 2005;Just and Gerhard 2004), deamidation (e.g., by E. coli cytotoxic necrotizing factor; Schmidt et al 1997;Flatau et al 1997), and transglutamination (Bordetella dermonecrotizing factor; Masuda et al 2000) resulting in inactivation or activation of the GTPases respectively (Fig. 2).…”
Section: The Targets Of C3-like Exoenzymes Are Molecular Switchesmentioning
confidence: 99%
“…In eukaryotic cells, CNF1 binds to its receptor, reported to be the receptor of laminin , and it is endocytosed and released into the cytoplasm by an acidic-dependent mechanism (Contamin et al, 2000). Once in the cytoplasm, CNF1 exerts its enzymatic activity that is represented by deamidation of a pivotal glutamine residue of the guanosine triphosphate (GTP)-binding proteins Rho, Rac, and Cdc42 (glutamine 63 of Rho or glutamine 61 of Rac and Cdc42), giving rise to a glutamic acid (Flatau et al, 1997;Schmidt et al, 1997;Lerm et al, 1999). The glutamine residue modified by CNF1 lies in the switch 2 domain of Rho proteins, which is involved in GTP hydrolysis; thus, the modification exerted by CNF1 blocks the Rho GTPases in their GTP-bound activated state.…”
Section: Introductionmentioning
confidence: 99%